2017
DOI: 10.1186/s12933-017-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

Incretin-based agents in type 2 diabetic patients at cardiovascular risk: compare the effect of GLP-1 agonists and DPP-4 inhibitors on cardiovascular and pancreatic outcomes

Abstract: BackgroundIncretin-based agents, including dipeptidyl peptidase-4 inhibitors (DPP-4Is) and glucagon-like peptide-1 agonists (GLP-1As), work via GLP-1 receptor for hyperglycemic control directly or indirectly, but have different effect on cardiovascular (CV) outcomes. The present study is to evaluate and compare effects of incretin-based agents on CV and pancreatic outcomes in patients with type 2 diabetes mellitus (T2DM) and high CV risk.MethodsSix prospective randomized controlled trials (EXMAINE, SAVOR-TIMI5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 69 publications
0
48
0
1
Order By: Relevance
“…As for DDP-4 inhibitors, the signal of harm was first identified in SAVOR-TIMI 53 and EXAMINE trials [47,48], in which heart failure hospitalization was increased with the use of saxagliptin and alogliptin. Furthermore, in several meta-analyses and observational studies, DPP-4 inhibitors were reported to be associated with an increased risk of worsening heart failure [49][50][51], besides acute pancreatitis and hypoglycemia [52]. Recently, the hypothesis of adrenergically mediated cardiotoxicity mediated by DPP-4 inhibition has been proposed [53].…”
Section: Discussionmentioning
confidence: 99%
“…As for DDP-4 inhibitors, the signal of harm was first identified in SAVOR-TIMI 53 and EXAMINE trials [47,48], in which heart failure hospitalization was increased with the use of saxagliptin and alogliptin. Furthermore, in several meta-analyses and observational studies, DPP-4 inhibitors were reported to be associated with an increased risk of worsening heart failure [49][50][51], besides acute pancreatitis and hypoglycemia [52]. Recently, the hypothesis of adrenergically mediated cardiotoxicity mediated by DPP-4 inhibition has been proposed [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter studies included relatively small numbers of patients with pancreatic cancer (13). A recent meta-analysis of the six largest randomized trials on incretin drugs obtained a summary relative risk of pancreatic cancer of 0.71 (95% CI 0.45-1.11) after 1.5-3.8 years of follow-up (14). However, the six trials analyzed reported a total of only 75 patients with pancreatic cancer, with a high level of heterogeneity of results across trials (I 2 = 61%).…”
mentioning
confidence: 99%
“…An observational study for multi-center (71 centers) demonstrated that 20 weeks of treatment with shortacting exenatide was well tolerated and showed a significant body weight and glucose reduction in T2DM patients whose glycemia had been inadequately controlled with oral hypoglycemic agents [21]. Once-weekly exenatide resulted in a nominal 9% relative reduction in major adverse cardiovascular events and a 14% relative reduction in all-cause mortality compared to placebo in T2DM with and without known cardiovascular disease [22], whereas dipeptidyl peptidase-4 inhibitors had no effect on cardiovascular risk outcomes but increased risks of acute pancreatitis and hypoglycemia [23].…”
Section: Discussionmentioning
confidence: 99%